Sustainable responses in metastatic melanoma patients with and without brain metastases after elective discontinuation of anti-PD1-based immunotherapy due to complete response - Dimitriou, Florentia; Zaremba, Anne; Allayous, Clara; Kähler, Katharina C.; Gerard, Camille L.; Festino, Lucia; Schäfer, Sarah; Toussaint, Frédéric; Heinzerling, Lucie; Hassel, Jessica C.; Ascierto, Paolo A.; Michielin, Olivier; et al. (European journal of cancer, 2021)
Background - Anti-PD1-based immunotherapy is currently used in most patients with advanced melanoma. Despite the remarkable data regarding overall survival, the optimal treatment duration is still unknown. - Methods - We evaluated the outcome of 125 patients with advanced melanoma with and without brain metastases (MBM), treated either with anti-PD1 monotherapy (N = 97) or combined with anti-CTLA4 (N = 28) after elective treatment discontinuation due to complete response (CR) (group A, N = 86), or treatment-limiting toxicity (N = 33) and investigator's decision (ID, N = 6) (group B) with subsequent CR. - Results - For group A, median duration of treatment (mDoT) was 22 months (range 5-49) and median time to CR 9 months (range 2-47). Accordingly, mDoT for group B was 3 months (range 0-36) and median time to CR 7 months (range 1-32). Seven patients from group A and three from group B experienced disease recurrence. Off-treatment survival was not reached. Median off-treatment response time (mOTRt) was 19 months (range 0-42) and 25 months (range 0-66), respectively. For MBM, mOTRt was 17 months (range 7-41) and 28 months (range 9-39), respectively. After a median follow-up of 38 months (range 9-70), seven (5.6%) patients had deceased, one (0.8%) due to melanoma. - Conclusions - Treatment discontinuation is feasible also in patients with MBM. Efficacy outcomes seemed to be similar in both groups of patients who achieved CR, regardless of reason for discontinuation. In patients who experienced disease relapse, treatment re-challenge with anti-PD1 resulted in subsequent renewed response.
Gesehen am 09.07.2021